Programming a GPS module - Vasudevan, Abinaya (2011)
This project is concerned with programming a GPS module that will be interfaced with a microcontroller. An application program was required to be written in C# language in order to support the necessary functions that are involved in interacting with the GPS receiver in the mobile phone. These functions would include, getting the coordinates, in other words, the latitude and the longitude, from the GPS receiver and computing the distance between two such coordinates. The GPS intermediate driver, which is a Windows Dynamic-Link Library (DLL) that provides a GPS application interface, was used to get the coordinates.